2017
DOI: 10.29252/ijrm.15.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intracellular anion superoxide level, heat shock protein A2 and protamine positive spermatozoa percentages in teratoasthenozoospermia

Abstract: Background:Teratoasthenozoospermia (TA) is a severe form of male infertility with no clear etiology.Objective:To compare the level of intracellular anion superoxide (O2–), heat shock protein A2 (HSPA2) and protamine deficiencies in ejaculated spermatozoa between teratoasthenozoospermic and normozoospermic men.Materials and Methods:In this case- control study, semen samples of 20 infertile men, with TA (with normal morphology lower than 4%_ and total motility lower than 40% ) as the case group and 20 normozoosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…We also found that in the two cohorts studied (N = 375 and N = 100), HDS was weakly correlated with CMA3. CMA3 directly competes with protamines in the sperm nucleus to bind GC-rich DNA domains, giving an indirect indication of protamine deficiency [50]. In addition, we show that HDS does not correlate at all with toluidine blue (TB) staining although some authors have reported the opposite [51].…”
Section: Discussionmentioning
confidence: 62%
“…We also found that in the two cohorts studied (N = 375 and N = 100), HDS was weakly correlated with CMA3. CMA3 directly competes with protamines in the sperm nucleus to bind GC-rich DNA domains, giving an indirect indication of protamine deficiency [50]. In addition, we show that HDS does not correlate at all with toluidine blue (TB) staining although some authors have reported the opposite [51].…”
Section: Discussionmentioning
confidence: 62%
“…According to SCSA data, both patient groups showed a significantly higher degree of DNA strand breaks in the sperm compared with the fertile individuals. Because increased reactive oxygen species and protamine deficiency are reported in UI and AT individuals (Mayorga‐Torres, Camargo, Cadavid, du Plessis, & Cardona Maya, ; Sabeti et al, ), we suggest that these factors may be responsible for DNA damages in our patients. In addition to DNA integrity, hyaluronic acid‐binding ability as a biomarker of cellular maturity could also influence the fertilizing potential of sperm.…”
Section: Discussionmentioning
confidence: 70%
“…Asthenoteratozoospermia is another common cause of male infertility in which, the failure of fertilization post‐ICSI could happen in a number of AT patients (Huang et al, ; Mangoli, Dandekar, Desai, & Mangoli, ). Although factors involved in the etiology of infertile men with asthenoteratozoospermia, such as genetic defects, DNA fragmentation, protamine deficiency, and oxidative stress, have been studied in the past (Avidan et al, ; Huang et al, ; Sabeti et al, ), the role of decreased expression and abnormal distribution of PLCζ, as a potential reason of male infertility, has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of O 2 ˉ generation were measured using dihydroethidium florescent dye 42,43 . With the exception of the third day, the superoxide ion production was incremented in both types of PCs during storage.…”
Section: Resultsmentioning
confidence: 99%